SUPERFLEX® LEARNING MODEL TO IMPROVE SOCIAL SKILLS - Huriah Rachmah (SAMPURASUN, 2016)
Social skills are the skills we use to Communicate and Interact with Each Other, both verbally and non-verbally, through gestures, body language and our personal appearance. Human beings are sociable creatures and we have developed many ways to Communicate our messages, thoughts and feelings with others. Social skills as the cognitive functions and specific verbal and nonverbal behaviors that an individual Engages in when interacting with others, Including both verbal and nonverbal skills. Behavior contained in the learners are not fully passed on just like that. When students think harder to solve problems, ask better questions, explain the answer in a more logical or hear with more attention, means that learners are in the process of learning. Problem inability of learners in social skills can be trained with Superflex® learning model where students are invited to become a social detective invited to do your own search problems regarding their behavior so as to become a social thinker and solve social problems.